Midsummer Trophic Overlap Between Guanaco and Sheep in Patagonian Rangelands - Pontigo, Felipe; Radic Schilling, Sergio Javier; Moraga, Claudio A.; Pulido, Ruben; Corti, Paulo (My University, 2020)
Diet overlap estimation among species is important to understand interspecific interactions. Through these interactions, one species may extinguish others through competition or adapt through mechanisms such as resource partitioning. The introduction of domestic herbivores in a native assemblage may introduce competition for resources with wild herbivores. In southern Patagonian steppes, guanaco (Lama guanicoe) populations are increasing after a drastic demise during the past century. This is occurring in protected areas and extensive ranching areas for sheep, and in the latter ranchers have rising concerns regarding competition. In this observational study, we measured diet overlap, food selection and preferences, and niche width for guanaco and sheep to compare use of food resources during the summer season. Feces were analyzed through microhistological technique to determine sheep and guanaco diets. Diets of guanaco and sheep were dominated by tussock grass (Festuca gracillima, sheep > 60%, guanaco > 50%), the most abundant plant species. Although food niche widths, measured through Levin's Index, were narrow, guanaco presented the broadest niche (P < 0.001). Of the 17 identified plant species present in guanaco and sheep diets, 5 were always selected by both ungulates and 1 was always avoided at the four study sites. Overlap between diets was high (> 0.90), evidencing potential competition. In addition, diet overlap coupled with our results of small variation in use and selectivity of food resources suggest the absence of resource partitioning. Therefore, both species might share resources or coexist, possibly due to high availability or spatial distribution of food resources and guanaco resilience to cope with numerically dominant competition from sheep. These findings offer new insight into the understanding of these species' interactions. It is also a management challenge to emerging wild and domestic herbivores interactions, as well as livestock production concerns at large. (C) 2020 The Society for Range Management. Published by Elsevier Inc. All rights reserved.
Keywords: coexistence; diet overlap; food resources; interspecific competition; patagonian grasslands; resource partitioning